DNSSEC Technology Development and Effect Analysis - Shutian Cui; Yue Liu (Dianxin kexue)
This article initiates the security problems on the domain name system, analyzes the DNSSEC technology and its security performance, introduces the process of DNSSEC and the trend in the global, points out the problems and deficiencies of the DNSSEC, and finally provides the strategy suggestion on the DNSSEC deployment in China.